Eagle’s Syndrome: Presentation, Diagnosis, and Management - Ashar Alamgir , Muhammad Musharaf Baig , Umair Ishfaq, Ashar Alamgir , Muhammad Musharaf Baig , Umair Ishfaq (Journal of Rawalpindi Medical College, 2020)
Objective: To study the presentation, diagnosis, and treatment options in Eagle’s Syndrome in a tertiary care hospital. Material and Methods: The study was conducted at the ENT department of District Headquarter Hospital, Rawalpindi from 1st January 2016 to 31st March 2019. All the patients who presented in outpatient (OPD) of the ENT department with pain around the ear and throat and diagnosed as a case of Eagle’s syndrome were included in the study. All the data of gender, age, CT scan findings, pain score, and management were noted on a predesigned proforma. Percentages and frequencies were calculated for all the data by using SPSS 21 version. Results: A total of 12 patients were included in the study, with 5 (42%) females and 7 (58%) males. The patient’s age range was from 24 to 68 years. Sharp, sudden onset, nerve-like pain was the major symptom in all cases. The length of the styloid process in 6 patients was between 3-4 cm and in 6 patients between 4-5 cm on a 3-dimensional computerized tomography scan. 100% of patients were managed surgically. In Group A (50%) styloidectomy was done after tonsillectomy while in other Group B (50%) patients styloidectomy was done by tonsil sparing technique. The relief of pain was a little better in patients of Group B. Conclusion: Sudden onset, sharp, shooting pain in the jaw area, around-ear, and in the throat with no other co-morbid should be investigated for Eagle’s syndrome. 3 dimensional CT scan is the best modality to see the length of the styloid process. Styloidectomy with tonsil sparing technique is a little better than tonsillectomy and gives early and permanent relief from this painful condition.